Frequency of Causes of Mortality Among Neonatal Age Group In Pediatrics Unit of Civil Hospital, Karachi - Fareed, Wajahat; Tauseef, Abubakar; Yamin, Mariam; Hussain, Abid; Godil, Ansab; Bugti, Anaam (International Journal For Research In Health Sciences And Nursing, 2016)
Objective: Frequency of Causes of Mortality among Neonatal Age Group In Pediatrics Unit of Civil Hospital, Karachi. Participants and Method: It was a statistical study, conducted at Pediatric Unit of Civil Hospital, Karachi. In this study all data was collected by the co-investigators during a period of 1 st January 2014 to 31 st December 2014,867 neonates were selected as these number of infants presented in the year 2014 in civil hospital, Karachi, and in the end data was analyzed by using SPSS 20.0 version. Results: Out of 867 neonates, 475(54.8%) were baby boys and 392(45.2%) were baby girls. The highest prevailing condition, being reason for admissions in both genders, was low birth weight, found in 116 boys and 96 girls. Out of 867 neonates admitted, 282 neonates suffered mortality with mortality percentage being 32.52%. Low birth weight (<2.5kg) caused largest number of mortalities (72 neonates), keeping in view their highest prevalence. The highest mortality ratio was found in preterm plus low birth weight (<1.5kg) neonates causing mortality in 46 out of 77 neonates admitted with this condition (59.74%) revealing the severity and lack of management of this condition. Conclusion: low birth weight appears to be the commonest cause of mortality among neonates in our locality. low birth weight not appears to be a great issue in first world countries like U.S.A, China and entire Europe but it appears to be a great threat to the lives of our neonates which can be prevented by improving the nutrition status of the pregnant females during their pregnancy, as by improving this we can save the lives of our neonates which are a precious part of one’s family.